Pengembangan Model Pembelajaran Akuntansi dengan Pendekatan Kontekstual - susilowati, eni (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2020)
Abstract: The purpose of this research and development is to produce a product in the form of a contextual accounting learning model that is packaged into teacher manuals and student manuals, this model is intended for class X students. This study used a design based research (DBR) approach. The data analysis technique used is descriptive quantitative and qualitative. Based on the results of research and development, the results of the responses of students at the time of the trial at SMAN 1 Kandat, Kediri Regency were 90.5%. This means that the contextual Accounting Learning Model can understand students about economic concepts that are in accordance with contextual learning, especially can make a meaningful learning that is intended for students